The development of Hand Sanitizer (HS) Production with Synthetic and Natural Scent Ingredients - Anugrah Ricky Wijaya; Irma Kartika Kusumaningrum; Daratu Kusuma Eviana Putri; Bayu Kreshna Adhitya Sumarto; Abdillah Al Farraby; Yusron Risqy Maulana; Puspa Rahmadina Lestari (Universitas Negeri Malang, 2021)
The effort of developed hand sanitisers (HS) production is needed in the era of the Covid-19 pandemic. The improvement of HS in terms of colour, aroma sharpness, and hand comfort is very important in the consideration of users choosing the HS product used. The socialisation of this service aims to report community service in creating HS production on a scale of 6 L/30 minutes using Propeller Mixing Hand Sanitizer (PMHS) by testing color, aroma, and hand comfort using synthetic and natural materials with chemical technology processes. The addition of the aroma of natural ingredients from fruit, flowers or seeds using maceration techniques from strawberry fruit, jasmine flowers, green tea leaves, and coffee grounds were extracted by the natural aroma liquid, which were added to HS products. The addition of HS products with the aroma of natural ingredients from strawberry, jasmine, green tea, and coffee was compared to the synthetic aromas of strawberry, jasmine, green tea, and coffee obtained from perfume shops. The questionnaire test of 44 respondents consisting of lecturers, staff, administration, and students for HS products evaluated color, aroma sharpness, and hand comfort. The results show that the colour, sharpness of the aroma and a sense of comfort in the hands of HS products with synthetic aromas of jasmine and green tea are highly favoured by users. These results were recommended as a reference for the manufacture and distribution of HS aromas of jasmine and green tea on a large scale.REFERENCESKualitas Gel Pembersih Tangan (Handsanitizer) Dari Ekstrak Batang Pisang Dengan Penambahan Alkohol, Triklosan Dan Gliserin Yang Berbeda Dosisnya.” Bioeksperimen 4(2):61–70.Anugrah Ricky Wijaya, Yudhi Utomo, Sumari, and Irma Kartika Kusumaningrum. “Pembuatan Hand Sanitizer Menggunakan PMHS (Propeller Mixing Hand Sanitizer).”HKI: 2019Diah JuliantariD, Ni Putu, Luh Putu Wrasiati, and Ni Made Wartini. 2018. “karakteristik ekstrak ampas kopi bubuk robusta (coffea canephora) pada perlakuan konsentrasi pelarut etanol dan suhu maserasi.” Jurnal rekayasa dan manajemen agroindustri 6(3):243. doi: 10.24843/JRMA.2018.v06.i03.p08.Golin, Andrew P., Dexter Choi, and Aziz Ghahary. 2020. “Hand Sanitisers: A Review of Ingredients, Mechanisms of Action, Modes of Delivery, and Efficacy against Coronaviruses.” American Journal of Infection Control 48(9):1062–67. doi: 10.1016/j.ajic.2020.06.182.Nazma Sabrina Sani, Rofiah Racchmawati dan Mahfud. 2012. “Pengambilan Minyak Atsiri Dari Melati Dengan Metode Enfleurasi Dan Ekstraksi Pelarut Menguap.” Jurnal Teknik Pomits 1(1):1–4.Riza Ibnu Fajar, Luh Putu Wrasiati*, Lutfi Suhendra. 2018. “kandungan senyawa flavonoid dan aktivitas antioksidan ekstrak teh hijau pada perlakuan suhu awal dan lama penyeduhan.” Jurnal Rekayasa Dan Manajemen Agroindustri 6(3):196–202.Septiani Mangiwa, Agnes Eri Maryuni. 2020. “Pengaruh Metode Ekstraksi Terhadap Sifat Fisik Dan Kimia Ekstrak Biji Kopi Sangrai Jenis Arabika (Arabica Coffea) Asal Wamena Dan Lanny Jaya.” AVOGADRO Jurnal Kimia 4(1):31–40.Shabri dan Dadan Rohdiana. 2016. “Optimasi Dan Karakterisasi Ekstrak Polifenol Teh Hijau Dari Berbagai Pelarut.” Jurnal Penelitian Teh Dan Kina 19(1):57–66.Sulusi Prabawati, Endang D. A., Suyanti, dan Dondy ASB. 2002. “Perbaikan Cara Ekstraksi Untuk MeningkatkanRendemen Dan Mutu Minyak Melati.” Jurnal Hortikultura 12(4):270–75.